Subphylum Crustacea Brünnich, 1772. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Ahyong, Shane T.; Lowry, James K.; Alonso, Miguel; Bamber, Roger N.; Boxshall, Geoffrey A.; Castro, Peter; Gerken, Sarah; Karaman, Gordan S.; Goy, Joseph W.; Jones, Diana S.; Meland, Kenneth; Rogers, D. Christopher; et al. (Zootaxa, 2011)
-